Pengaruh Metode Problem Based Learning dengan Media Wattpad terhadap Keterampilan Menulis Cerpen Siswa - Putri Anjani; Dessy Wardiah; Yenny Puspita (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study was prompted by the low short story writing skills observed among students at Sriwijaya State Sports Senior High School. The purpose of this research was to examine the effect of applying the Problem-Based Learning method integrated with Wattpad as a learning medium on improving students' short story writing skills. A quasi-experimental approach was employed using a pre-test–post-test control group design. The sample consisted of 46 eleventh-grade students selected randomly, with 31 assigned to the control group (conventional learning) and 15 to the experimental group (PBL-Wattpad). Data were collected through short story writing tests administered before and after the intervention, and were analyzed using paired t-tests and independent t-tests at a significance level of 0.05. The results indicated an average score improvement of 26 points in the experimental group (from 57 to 83), which was higher than the control group’s gain of 11 points (from 50 to 61). The Paired Sample t-Test and Independent Sample T-Test yielded p-values < 0.05, indicating a statistically significant difference. The improvement encompassed aspects of creativity, plot development, structure, and language use. These findings demonstrate that the integration of Problem Based Learning and Wattpad is effective in enhancing students’ short story writing skills by fostering a contextual and collaborative learning environment, while also offering authentic feedback from readers. Practically, Indonesian language teachers are encouraged to adopt this strategy to promote both creative and digital literacy at the high school level.